Bending properties of structural foams manufactured in a hot press process. (8th September 2022) - Salmins, Maximilian; Mitschang, Peter
Abstract: Thermoplastic foams allow manufacturing of lightweight parts with good thermal and acoustic insulation properties. To increase the mechanical properties without changing the part weight, these foams can be transformed into structural foams by a newly developed two-step isochoric and isothermal hot press process. Structural foams consist of a low-density foam core and two high-density polymer skins. The production of a polymer skin on the surface of a foam was realized in a hot press process by heating one tool half to process temperatures above glass transition temperature of the amorphous polymer. To manufacture polymer skins on both sides of the foam, it is necessary to turn the foam upside down and repeat the procedure. Structural foams were manufactured with two different polymer foams with different cell structures and densities. Optical analysis of microsections was used to investigate the formation of the polymer skins and the change in foam structure. This study investigates the applicability of an empirical relationship between part densities and bending properties. It was found, that knowledge about the part density alone is not sufficient for the prediction of the bending properties, because the foam structure (e.g. open or closed foam cells) has a considerable impact on the foam properties. Graphical Abstract: UF0001